2000
DOI: 10.1097/00004872-200018060-00002
|View full text |Cite
|
Sign up to set email alerts
|

Role of oxidative stress in cardiovascular diseases

Abstract: The existing evidence support the view that oxidative stress may play a crucial role in cardiac and vascular abnormalities in different types of cardiovascular diseases and that the antioxidant therapy may prove beneficial in combating these problems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
842
3
22

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 1,246 publications
(901 citation statements)
references
References 243 publications
9
842
3
22
Order By: Relevance
“…It has been already reported that oxidative stress provoke DNA damage (DNA fragmentation and apoptosis) and treatment with antioxidants inhibit DNA fragmentation and apoptosis [32] . Oxidation of catecholamine forms quinonoid compounds giving rise to the production of superoxide anions and subsequently hydrogen peroxide, which in the presence of iron forms highly reactive hydroxyl radicals and causes protein, lipid and DNA damage [33] . Further, increased expression of iNOS in myocardium of animals and patients with heart failure may be responsible for increased numbers of apoptotic cardiomyocytes [34] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been already reported that oxidative stress provoke DNA damage (DNA fragmentation and apoptosis) and treatment with antioxidants inhibit DNA fragmentation and apoptosis [32] . Oxidation of catecholamine forms quinonoid compounds giving rise to the production of superoxide anions and subsequently hydrogen peroxide, which in the presence of iron forms highly reactive hydroxyl radicals and causes protein, lipid and DNA damage [33] . Further, increased expression of iNOS in myocardium of animals and patients with heart failure may be responsible for increased numbers of apoptotic cardiomyocytes [34] .…”
Section: Discussionmentioning
confidence: 99%
“…The heart was transversely cut across the left ventricle to obtain slices no more than 0.1 cm in thickness. The heart slices were placed in the covered, darkened glass dish containing pre warmed (1%) TTC solution in phosphate buffer and the dish was incubated between 37-40 曟 for [30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45] min. the heart slices were turned over once or twice to make certain that it remains immersed and covered by 1 cm of the TTC solution.…”
Section: Macroscopic Enzyme Mapping (Ttc Staining)mentioning
confidence: 99%
“…Cardiomyocyte ETC dysfunction leads to excessive generation of ROS that causes heart malformation and lethality (Ingraham et al, 2009). ROS play an important role in the pathogenesis of a variety of cardiovascular diseases such as hypertension, cardiomyopathy, cardiac hypertrophy, heart failure and ischemia-reperfusion injury (Ytrehus et al, 1987;Dhalla et al, 2000). Thus, ROS and their origin ETC are vital cellular components in the maintenance of cardiac function.…”
Section: Reactive Oxygen Species (Ros) Play An Important Role In Regumentioning
confidence: 99%
“…Catecholamines are known to be a major risk factor for hypertension and CVD, because they can increase heart rate, blood pressure and ROS production. [67][68][69][70] Elevated catecholamines may be caused by two factors: (1) an increase in catecholamines release from the sympathetic nervous system and (2) a decrease in their degradation (that is, inactivation). Methylation is a crucial step in the degradation of catecholamines, which involves two methyltransferases: phenylethanolamine N-methyltransferase and catechol O-methyltransferase, where the former catalyzes norepinephrine to epinephrine and the latter converts catecholamines to methylated derivatives.…”
Section: Arsenicmentioning
confidence: 99%